2021
DOI: 10.3390/plants10071291
|View full text |Cite
|
Sign up to set email alerts
|

A Transcriptional Analysis of the Genes Involved in the Ascorbic Acid Pathways Based on a Comparison of the Juice and Leaves of Navel and Anthocyanin-Rich Sweet Orange Varieties

Abstract: Sweet oranges are an important source of ascorbic acid (AsA). In this study, the content of AsA in the juice and leaves of four orange clonal selections, different in terms of maturity time and the presence/absence of anthocyanins, was correlated with the transcription levels of the main genes involved in the biosynthesis, recycling, and degradation pathways. Within each variety, differences in the above pathways and the AsA amount were found between the analysed tissues. Variations were also observed at diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
15
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 92 publications
5
15
1
1
Order By: Relevance
“…Moreover, the absence of light markedly repressed the expression of GalUR8, and also GalUR12 in some species, concomitantly with the reduction of AsA concentrations in the flavedo [23]. These findings support the notion that the D-galacturonic acid plays an important role in AsA accumulation in Citrus fruits [19,21]. Information of AsA metabolism in Citrus organs other than fruits is very limited and mainly restricted to the analysis of enzymatic activities of AsA degrading and recycling enzymes under stress conditions [24][25][26][27][28].…”
Section: Introductionsupporting
confidence: 77%
See 4 more Smart Citations
“…Moreover, the absence of light markedly repressed the expression of GalUR8, and also GalUR12 in some species, concomitantly with the reduction of AsA concentrations in the flavedo [23]. These findings support the notion that the D-galacturonic acid plays an important role in AsA accumulation in Citrus fruits [19,21]. Information of AsA metabolism in Citrus organs other than fruits is very limited and mainly restricted to the analysis of enzymatic activities of AsA degrading and recycling enzymes under stress conditions [24][25][26][27][28].…”
Section: Introductionsupporting
confidence: 77%
“…Nonetheless, Alós et al [19] suggested the importance of the D-galacturonic acid and the myo-inositol pathways in the regulation of AsA accumulation in Citrus fruit tissues, with the genes D-galacturonic acid reductase12 (GalUR12) and myo-inositol oxygenase (MIOX) playing a key role. More recently, Caruso et al [21] associated the decrease in AsA content in the juice of blood oranges during maturation to the down-regulation of MIOX and GalUR12, together with GDP-mannose-3 ,5 -epimerase (GME) and L-Galactose dehydrogenase (GalDH) of the L-galactose pathway. Interestingly, these authors also proposed that the contribution of the different biosynthetic pathways to the AsA pool varied during fruit development, with the L-galactose and myo-inositol being important at the early stages of fruit development and the L-gulose pathway at the end of ripening [21].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations